Interpreting and Living God's Law at Qumran Migsat Ma'ase Ha-Torah, Some of the Works of the Torah - Kratz, Reinhard Gregor; Tigchelaaar, Eibert (Mohr Siebeck, 2020)
The text Miq?at Ma?a?e Ha-Torah, Some of the Works of the Torah (4QMMT), is one of the most interesting texts among the famous Dead Sea Scrolls discovered near the settlement of Khirbet Qumran and its vicinity in the middle of the twentieth century and by now published in full. It is a writing in the form of a letter by an unknown author to an equally unknown addressee, written in second person singular and plural. This document is the earliest evidence of a proper interpretation of the Jewish Torah, the so-called Halakhah, from pre-Christian, Hellenistic times as it later became customary and widely attested in rabbinical Judaism. This volume - after a short introduction on the findings at the Dead Sea in general and the text Miq?at Ma?a?e Ha-Torah in particular - provides a new edition and translation as well as several contributions from renowned scholars on the manuscripts, the language and content plus literary and historical contexts of this writing.